Relationship between various jump performances and running performance during the 60 m-sprint in female athletes: Focus on the leg action of the single leg jump and the running velocity - Shiga, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2013)
The purpose of this study was to investigate the relationship between running performance and both vertical and horizontal jump performance, and also the relationship between leg action in the horizontal jump and running velocity, and jump distance. The subjects were 17 female athletes (Mean±SD; Age 18.6±0.7 years; Height 160.7±3.8 cm; Weight 55.8±5.1 kg) who performed 60-m sprint from a block start, various vertical and horizontal jumping tasks, such as 5-stepping and 5-hopping in a horizontal direction, and Squat jump (SQJ) and Drop jump (DJ), and 10-Rebound jump (RJ10) in a vertical direction. The main results were as follows: (1) Various jump tasks, such as performance in the 5-stepping, 5-hopping, SQJ, DJ, and RJmax, in descending order, were shown to have a high correlation with the average 60-m running velocity. (2) Ability in the horizontal single leg jump showed a high correlation with running velocity in each phase over 10-60-m. (3) Significant correlations were found between jump distance in the 5-stepping, and 5-hopping and step frequency, and step length during the 30-40-m. (4) The 5-stepping and 5-hopping were important for the swing motion of the free leg during the contact phase to improve running velocity and jump distance. (5) The 5-hopping was important for leg flexion of the hip joint during the first flight phase, and for leg extension of the hip joint during the final flight phase, thus improving running velocity. These results indicated that various jump tasks in femele athletes were an effective training method to improve running velocity in 60-m. Especially, a horizontal jump with a single leg showed a higher correlation than a vertical jump with both legs. Additionally, it was clearly shown that 5-stepping and 5-hopping were important for swinging the free leg forward in the contact phase, especially the 5-hopping was important for swinging the right and left legs in the flight phase to improve running performance in female athletes.